SOCIAL MEDIA AND POLITICAL PARTICIPATION: AN ANALYSIS OF YOUTH ENGAGEMENT IN ONLINE AND OFFLINE ACTIVISM - Claire Camilleri; David Zammit; Caroline Borg (Cognitionis Civitatis et Politicae, 2026)
Indonesia’s decentralization and regional autonomy reforms, implemented in the early 2000s, aimed to enhance local governance and improve public services. However, these reforms have led to varying outcomes across Indonesia's provinces, with significant disparities in the quality and accessibility of public services. This study investigates how decentralization has influenced public service delivery and governance challenges in different regions, highlighting the uneven impacts of these reforms. This research aims to analyze the disparities in public service delivery across Indonesian provinces and the governance challenges resulting from the decentralization process. The study seeks to understand the factors contributing to these disparities and their implications for regional development and equity in public service provision. A mixed-methods approach was employed, combining quantitative data analysis from national and regional reports with qualitative interviews with local government officials and community leaders. The study examines key indicators of public service performance, such as healthcare, education, and infrastructure, across various provinces. The study reveals significant disparities in public service delivery, with wealthier and more urbanized provinces exhibiting better outcomes. Meanwhile, poorer and more remote regions face challenges in governance capacity and resource allocation, leading to uneven public service provision. The decentralization process in Indonesia has had mixed results, with regional autonomy contributing to greater governance flexibility but also deepening disparities in public service quality. Further reforms are necessary to address these inequities and strengthen local governance capabilities.